The Determination of Tourist Expenditures to the Tourism Object of Gibeon Hill, Tobasa Regency - NAPITUPULU, Junika; MANULLANG, Marihot (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
The presence of tourism will grow economic businesses that regulate and support tourism activities so it can be increased people's income. Riau Islands Province is one of tourism center that offers a variety of tourism destinations such as beautiful lakes, natural attractions and naturalsceneries. Tourism object of Gibeon Hill, TobasaRegency is one of the interesting natural attractions, supported by natural scenery as a popular tourism object that has not been managed properly. This study was conducted to analyzetourist expenditures on thetourism object of Gibeon Hill, Tobasa Regency. This studywas a quantitative descriptive analysis with the sampleas many as 115 people who are tourists with random sampling techniques. The results of the study were 1). Income has a significant effect on tourist expenditures to the tourism object of Gibeon Hill, Tobasa Regency and it was a dominant variable that effected on tourist expenditures to the tourism object of beach in Tanjung Pinang.2).Mileage has a significant effect on tourist expenditures to the tourism object of Gibeon Hill, Tobasa Regency, 3). Information Sources has a significant effect on tourist expenditures to the tourism object of Gibeon Hill, Tobasa Regency, 4). Vehicles Used has a significant effect on tourist expenditures to the tourism object of Gibeon Hill, Tobasa Regency and 5). Consumption has a significant effect on tourist expenditures to the tourism object of Gibeon Hill, Tobasa Regency. Suggestions for the studywere: 1). The Local Government of Tobasa Regency was suggested to be able to improve tourism management by prioritizing culture, naturalness of tourism objects, and improving infrastructure to the tourismobject, 2)For the Manager of Gibeon Hill tourism object, Tobasa Regency was suggested to pay attention to people in the neighborhood sightsGibeon Hill, Tobasa Regency by motivating community, banking cooperation in increasing people's income, making a breakthrough in the form of information on social media and encouraging tourism entrepreneurs and BPW to collaborate in promoting tourism in the Gibeon Hill, Tobasa Regency.